Peran Orang Tua dalam Pembelajaran Daring di SMK 2 Respati Jakarta - Junita Yosephine Sinurat (Neolectura, 2021)
Online learning is distance learning that utilizes telecommunications and information technology. Online is used as a learning model during the corona pandemic to anticipate the spread of the Covid-19. In the learning process this is less effective because there is still a lack of parental roles in mentoring, supervising and motivating children while attending school from home. Parents are the first and foremost educators in the family environment. The purpose of this study was to find out how the role of parents in online learning at SMA Respati Jakarta and what obstacles were encountered in assisting children during learning. The research used is a qualitative descriptive study. data collection was done through filling out online questionnaires via google form, and interviews. The results showed that parents play a very important role in the teaching and learning process during learning from home. Where parents act as motivators, facilitators in accompanying and teaching materials that have not been maximally delivered by teachers due to limitations during this pandemic.